Triple Pillar for Sustainability of Accounting Evaluation of Carbon Emissions and Climate Change - Alsayed, Huda (International Journal of Economics and Financial Issues, 2024)
This study is among the first to address the relationship between accounting and adaptation to climate change. Aramco is a well-known company in the Middle East that produces oil, and it was used as a case study. This study examines the theoretical underpinnings of accounting assessment of carbon emissions arising from climate change and their influence on sustainability. The questionnaire was distributed to approximately 150 Saudi Arabian managers. The researcher used an analytical descriptive technique and the Statistical Packages Program for Social Sciences (SPSS) to assess the sample, fill out, tabulate, analyze the data, and test the hypotheses. The findings demonstrate that accounting for carbon emissions affects sustainable development in its three pillars-economic, social, and environmental. Further, the sub-hypothesis’s results indicate that accounting for carbon emissions statistically impacts sustainable development’s economic and environmental aspects. Accounting for carbon emissions has no discernible impact on sustainable development through the social component. The researcher advocated that the social aspect of sustainable development should be given attention. Large corporations are made aware of their significance in achieving environmental sustainability and that failing to adopt labor and human rights standards will result in companies being held accountable.